Reflexivity and the ability to predict activities as the basis for future professional personality formation - Elena N. Chekanushkina; Elena B. Gulk (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the context of dynamic transformations in all spheres of activity, the particular importance of professional’s abilities for reflexive and prognostic activity in adapting to new challenges is obvious. Future professionals need the ability to solve non-standard tasks, cope with emerging problems, control their own actions, readiness for objective assessment of work results, self-education and professional development. The aim of the research is to define the essence and content of the reflective and prognostic abilities of an individual, their significance in professional activity, as well as to identify the level of development of these qualities among university students in psychological-pedagogical and technical fields of study, and to outline the conditions for their productive development. The authors carried out a theoretical analysis of the definitions of «reflexivity» and «forecasting», reflected in numerous psychological and pedagogical studies of interdisciplinary focus by scientists from different countries. The relationship between reflexive and prognostic abilities with self-regulation of behavior and activity of an individual, their adaptation and professionalization were revealed. Diagnostics were conducted to determine the level of reflexivity (suggested by A.V. Karpov, V.V. Ponomareva) and the prediction ability (suggested by L.A. Regush) among first-year students of the psychological and pedagogical fields of study at Peter the Great St. Petersburg Polytechnic University and the technical field at Samara State Technical University. The results of psychodiagnostics of reflexive and predictive abilities of students are presented and indicate an insufficient level of predisposition to retrospective, situational, prospective reflection and forecasting. However, the implementation of an integrated approach in classroom and extracurricular training, the use of intensive pedagogical technologies (practice-oriented, heuristic, informational) in the educational process, the problem solving techniques and test material developed on the basis of the matrix model of cognitive activity during intermediate monitoring showed positive dynamics in the increase of the level of development of reflexive and predictive student abilities.